From Vision to Action: Unraveling Work Engagement’s Role in Linking Leadership to Performance - Rezeki, Fitri; Badrianto, Yuan; Wijayanto, Tri Ngudi; Wulandari, Anna; Ramadhani, Yunita (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2024)
Objectives- This study aims to analyze the effect of transformational leadership style on employee performance by involving work engagement as a mediating variable at CV Mustika Jaya Furniture. Methodology- The study used a quantitative approach with a survey method of 74 employees of CV Mustika Jaya Furniture selected by purposive sampling. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS V3.0 software to test the mediating role of work engagement and the validity and reliability of the model. Findings- The results of the study indicate that: (1) transformational leadership style has a positive and significant effect on employee performance, (2) transformational leadership style has a positive and significant effect on work engagement, and (3) work engagement acts as a partial mediator in the relationship between transformational leadership and employee performance. Suggestion- Theoretically, this study strengthens the empirical evidence on the mediation mechanism in the leadership-performance relationship in the context of Indonesian furniture SMEs